PROFILE OF ULCUS DECUBITUS PATIENTS WHICH ARE ON BED REST AT HOSPITAL IN THE CITY OF MEDAN - Syapitri, Henny; Sinurat, Lasma Rina Efrina; Marbun, Agnes Silvina (Jurnal Ilmiah Keperawatan, 2024)
A study shows pressure ulcers are a secondary affliction that is experienced by many hospitalized patients, especially the patients with chronic diseases and patients who are very weak. However, the most frequently reported risk factors are older age, stay longer in the ICU, cardiovascular disease history, diabetes and stroke. This study aims to identify the profile of ulcers decubitus sufferers at Adam Malik General Hospital Medan and Hermina General Hospital Medan. The research method uses a quantitative descriptive approach. Data was collected using observation sheets and medical records. Sampling was done by chance with a total of 104 samples. Analysis of the data used is univariate analysis. Based on the results of the study, it wasfound that the average age of decubitus patiens was 55 years. The majority of decubitus patients are female is 55.8%. The patient’s average weight is 77 kg, average height is 161 cm, and the average body mass index is 24.8 (overweight). Based on the ulcer grade the majority is grade 2 with a percentage of 57, the average length of patient stay is 7 days. The diagnoses that led to 104 patients on bed rest varied widely. Most diagnoses were stroke (neurological disease) with a total of 48.1%.